Long-Covid in Children and Adolescents: Clinical Challenges and Treatment Perspectives - Karamus, Kornelia; Rejamak, Rafał; Biłogras, Jan; Borowska-Łygan, Martyna; Strużek, Konrad; Urban, Wojciech; Tomaszewski, Jakub (Journal of Education, Health and Sport, 2025)
Introduction: Long COVID is a complication of the coronavirus disease. As a relatively new medical condition, it presents challenges in establishing consistent principles for its classification, diagnosis, and treatment. Objective: The aim of this paper is to review the current knowledge regarding the new medical condition known as Long COVID in children. Materials and Methods: The review includes works published between 2020 and 2024, available in the PubMed database, identified using relevant keywords, as well as the WHO publication "World Health Organization. A clinical case definition for post COVID-19 condition in children and adolescents by expert consensus, 16 February 2023." Results: The literature review revealed that Long COVID is a relatively common issue, affecting up to 25.24% of children and adolescents. Identified risk factors include age over 10 years, severe primary infection, MIS-C, female gender, allergic diseases, obesity, living in polluted areas, comorbidities, poor physical and mental health, and prior respiratory infections. The spectrum of LC symptoms is broad and includes many nonspecific manifestations. The diversity of symptoms complicates diagnosis and necessitates a more holistic approach to patient care. Treatment of LC in children also poses a challenge. Most available studies focus on adults, with limited reports suggesting the efficacy of lactoferrin in managing gastrointestinal symptoms of LC in children. Physical activity is also suggested as an effective rehabilitation method for addressing reduced physical capacity and chronic fatigue. Conclusions: There is an urgent need for large-scale studies on the risk factors, causes, symptoms, and treatment of LC in children and adolescents. Developing cohesive guidelines would improve patients’ quality of life, facilitate diagnosis, and streamline treatment processes.